Loanwords in BBC Arabic Instagram - Tika Fitriyah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
A study of the use of language in society or the media needs to be done to see linguistic phenomena that are always dynamic. This research was descriptive-qualitative research that aimed to describe and analyze loanwords from foreign languages in BBC Arabic Instagram. The data were taken using the observation method with the uninvolved conversation observation technique (Simak bebas libat cakap) using the purposive sampling technique. The results showed that the absorption form in BBC Arabic Instagram is dominated by a direct absorption model by adapting phonological and morphological adaptations. The research also showed that social media preferred to use foreign language absorption words directly even though these words had Arabic equivalents. The excessive use of foreign terms and out-of-control was feared to cause the death of some words in Arabic and the collapse of the sovereignty of the Arabic language because it was colonized by other languages with more advanced civilizations. Keywords: loanwords, phonology and morphology adaptation, social media